PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PENERIMAAN BEASISWA UNTUK MAHASISWA DENGAN METODE SAW - Muhammad Reza Maulana; Suhendri ST (PROCEEDING STIMA)
Majalengka University is a private university that has many outstanding students. Unfortunately there are some among them who have difficulty education expenses. Then held a government program in the form of scholarships to help ease the financial burden for underprivileged students at the University of Majalengka, it is intended for outstanding students but have financial difficulties. As for the criteria that should be owned by the grantee is a good achievement, having virtuous behavior, and belong to poor families. At the University of Majalengka no support system to help to select from the many students who are eligible for the scholarship, it is necessary to build a decision support system that will help determine who gets the scholarship so that more accurate in determining the criteria each student to receive a scholarship , The model used in this Decision Support System is Simple Additive Weighting (SAW), SAW is chosen because it can determine the weight values for each attribute, followed by the ranking process that will select the best alternative from a number of alternatives, in this case the alternative question is that entitled to receive scholarships based on criteria specified.Keywords : DSS, SAW, Scholarship